Gestational hormone trajectories and early pregnancy failure: a reassessment - Paul G Whittaker; Courtney A Schreiber; Mary D Sammel (BMC, 2018)
Abstract Background Studies have commonly assessed the endocrinolgical status of women once miscarriage is threatened or suspected; few studies have explored the antecedent hormonal environment or used a longitudinal strategy. Using refined statistical techniques, we sought to re-evaluate whether gestational hormone trajectories in early pregnancy can identify future miscarriage in asymptomatic pregnancies. Methods This prospective cohort study followed 105 women over-conception; 72 had normal term pregnancy outcomes while 33 experienced early pregnancy failure between 35 and 115 days of gestation. Participants attended a pre-conception and antenatal clinic at Newcastle University, United Kingdom (UK). Evaluation methods included ultrasound, clinical assessments of pregnancy progress and serial measurements of gestational hormones by radioimmunoassays. Linear mixed-effects regression analysis examined hormone relationships with pregnancy outcomes. Results Detailed longitudinal illustration of gestational hormones, antecedent to miscarriage indications, revealed early pathophysiological trends. In particular, oestradiol showed as marked a deviation from normal as progesterone before miscarriage was evident, reflecting a deficiency in the ovarian response to rising human chorionic gonadotrophin (hCG) levels. Regression analysis provided equations for gestational hormone slopes that significantly differentiated asymptomatic women with subsequent early pregnancy failure, compared to women with normal term pregnancies. Both progesterone and oestradiol displayed negative mean slopes in pregnancies destined for failure; in this group, both human placental lactogen (hPL) and hCG revealed mean positive trajectories that imitated normal pregnancies but at slower rates of increase. Conclusions Oestradiol, progesterone and hCG trajectories, from 50 days of gestation, have good potential for revealing pathophysiology and for identifying which asymptomatic pregnancies are destined for subsequent failure. In asymptomatic patients where there is concern about viability and ultrasound diagnosis is ambiguous, a combined hormonal profile could contribute to guiding patient care decisions.